Avaliação do efeito anticonvulsivante neuroprotetor de N-metil-(2S,4R)-trans-4-hidroxi-L-prolina isolada de Sideroxylon obtusifolium (Humb. Ex Roem. & Schult.) T.D. Penn. : relação com o teor de L-prolina da molécula - Aquino, Pedro Everson Alexandre de (2021)
Epilepsy is a chronic neurological disease characterized by recurrent seizures, resulting from excessive neuronal discharges. Considering that inflammatory processes and oxidative stress are related to their pathogenesis, we investigated the possible anticonvulsant effects of a derivative of the amino acid proline from Sideroxylon obtusifolium, (also known as quixaba, black quixaba, sapoteiaba, hawthorn, coronet) - (2S, 4R) -trans-4-hydroxy-L-proline, (NMP) in the seizure-induced model of pilocarpine and pentylenetetrazole (PTZ), as well as in the state-epileptic model (status epilepticus or SE) using the pilocarpine via intracerebroventricular- (icv), in mice. In-parallel tests were performed in vitro using secondary lineage of astrocytes and in silico molecular modeling tests (using software and computational models). For this, the mice were distributed into groups treated orally with NMP (50, 100, and 200 mg/kg) and their controls (The control group received saline). The behavioral parameters were: latency time for the first seizure and time of death. Also, immediately after death, brain areas were dissected for biochemical analysis. In the SE model, the effects of NMP (100 and 200 mg/kg) were evaluated in behavioral tests by characterizing the preservation of cognitive function (Y-labyrinth tests and object recognition). The viability of the hippocampus cells was determined by Nissl staining. Additional markers of cell damage have been studied, such as glial fibrillar acid protein (GFAP); expression of the calcium-binding adapter molecule 1 (Iba-1), and caspase 3, using, respectively, immunofluorescence and western blot analyzes. Our results demonstrate that latency to first seizure and latency to death increased in groups pre-treated with NMP, compared with control groups. Besides, the reductions in the concentrations of Dopamine and its striatal metabolite observed in the pilocarpine group were partially reversed in the NMP groups. GABA concentrations decreased and glutamate concentrations increased after using pilocarpine, and these changes are also reversed by NMP. Likewise, NMP significantly reduced brain oxidative stress seen in the pilocarpine-treated group. The increases in hippocampal expressions for IL-6 and IFN-gamma, observed after pilocarpine administration, were reversed by NMP, as well as the increase in GFAP expression. In the model using pilocarpine via icv, it induced cognitive deficits, cell damage, increased expression of GFAP, Iba-1 eGAT1 in the hippocampus. These changes were prevented by the NMP. In in vitro tests, there was protection from cell death, less mitochondrial damage, and less GFAP expression in cells treated with NMP. We also performed molecular coupling experiments revealing that NMP binds to transporter 1 of aminobutyric acid (GABA) (GAT1), and the expression of GAT1 in the hippocampus was also characterized. In conclusion, we demonstrate the significant anticonvulsant and neuroprotective effects for NMP that are probably related to the L-proline content present in this methanolic fraction (NMP), with the anti-inflammatory and antioxidant properties of this bioactive component and/or its interaction with GAT-1.